Potential productivity of hydroponically-grown tomatoes ill the Genting Highlands, Malaysia - Raja Harun, Raja Muhammad (Universiti Pertanian Malaysia, 1989)
Five trials were carried out to assess the potential productivity of tomatoes in a deep culture hydroponic system in Genting Highlands (1,200 m a.s.l.), Malaysia. The tomatoes were maintained as single-stemmed plants using the layering and vertical methods of plant training. Determinate and indeterminate varieties producing large, medium and small-sized fruits were investigated in these trials. Under the layering system, the indeterminate plants could last for nine months but if crops were kept for only six months, two crops per year could be produced with a potential yield of 252-288 ton/ha/year. The vertical system could produce three crops per year with a range of 21 0-248 tonnes/ha/year for the three sizes of fruits. The determinate varieties produced a wide range of yields and, with three crops per year, a yield range of 131-216 ton/hal could be expected. The yields obtained in the tested hydroponic system were at least five to ten times higher than those obtained from traditional soil cultivation under highland and lowland conditions in Malaysia.